Kiểm chứng tác động của kiều hối tới tăng trưởng kinh tế Việt Nam dựa trên mô hình ARDL - Phạm Thị Hoàng, Anh; Phạm Đức, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
The paper aims at investigating the impact of remittance flow on economic growth in Vietnam. By employing the Auto-regressive Distributed Lag (ARDL) model for quarterly data series in the period of 1996–2016, the study shows a long-term nonlinear inverted U-shaped relationship between remittances and economic growth in Vietnam. It means that remittance inflow at a certain level can promote economic growth through the improvement of investment capital and labours, the development of financial intermediary operations, and consumption enhancement. However, it is possible to have the negative effect in the case of excessive remittance inflows which may cause moral hazard and the consequences of "Dutch disease" problems. In addition, no new evidences of the financial development’s moderating role in the remittances – growth nexus in Vietnam have been found.